Current opinions on autophagy in pathogenicity of fungi. Issue 1 (1st January 2019) - Zhu, Xue-Ming; Li, Lin; Wu, Min; Liang, Shuang; Shi, Huan-Bin; Liu, Xiao-Hong; Lin, Fu-Cheng
ABSTRACT: The interaction between pathogens and their host plants is a ubiquitous process. Some plant fungal pathogens can form a specific infection structure, such as an appressorium, which is formed by the accumulation of a large amount of glycerin and thereby the creation of an extremely high intracellular turgor pressure, which allows the penetration peg of the appressorium to puncture the leaf cuticle of the host. Previous studies have shown that autophagy energizes the accumulation of pressure by appressoria, which induces its pathogenesis. Similar to other eukaryotic organisms, autophagy processes are highly conserved pathways that play important roles in filamentous fungal pathogenicity. This review aims to demonstrate how the autophagy process affects the pathogenicity of plant pathogens.